E-Governance and Civic Technology: Lessons from Taiwan - John Biberman (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
For decades, Taiwan has demonstrated itself to be among the world's leaders in implementing e-government systems which improve efficiency, transparency, and representation for the entire population. Taiwan's response to the COVID-19 pandemic, which leaned heavily on these e-government systems and was one of the best in the world, has amply demonstrated this. Specifically, Taiwan's whole-of-government approach to implementing digital innovations in all aspects of governance has caused it to stand out from the crowd. Its unique approach to ICT has encouraged greater civic participation and a partial erasure of the traditional boundary between government and the citizenry. By allowing government to take advantage of the latent ICT skillsets of its citizens, Taiwan has created a more responsive, effective policy formulation and implementation mechanism which can likewise be taken advantage of by other societies with similar human resources at their disposal. Namely, India, with its large national reservoir of trained coders, would benefit substantially from following the Taiwanese model in implementing its own e-governance initiatives.
Keywords: 330